Care of the imminently dying - Paice, Judith A. (HPNA palliative nursing manuals, 2016)
"Provides an overview of symptom management when a patient is reaching the end of their life. This volume covers delirium and the advantages of early diagnosis, determining the presence of dyspnea, death rattle, or cough, urgent syndromes that may appear at the end of life, palliative sedation, and the withdrawal of life-sustaining therapies."--Book cover